An Analytical Study of the Drama "PINJRA" In Descriptive Context - Mobeen, Saher; Butt, Muhammad Afzal (sourcecoder, 2024)
Children are the future and capital of any nation. That is why positive education and healthy personality of children is very important for the development of any society. The most important and basic role in the development of children’s personality is the role of parents. Because the attitude of the parents and the environment of the house decides the future of children either it will be positive or negative. If the environment of house and parent’s attitude will be friendly the child will definitely have a strong personality. But if the environment of the house will consist negative and unnecessary closures, then the children will suffer from negative psychological problems. And the psychological pain or problems found in childhood affect the memory and personality of a person until death.